Analysis of Perceptions of Community Co-Management by Households in the Surrounding Communities of Protected Areas: Empirical Study of Xishuangbanna National Nature Reserves in China - Changhai Wang; Ao Li (Land)
How to coordinate the relationship between nature reserves and surrounding communities to achieve a win–win situation for protection and development has become an urgent issue that governments around the world need to address. The concept of community co-management emerged in this context, aiming to promote cooperation and interaction between protected areas and surrounding communities, achieve sustainable use of natural resources, and promote the healthy development of the community economy. This study conducted empirical analysis using the Xishuangbanna National Nature Reserve and surrounding communities in China as a case study. This study aims to reveal the key factors affecting the perception of the households in the surrounding communities of the national nature reserve through an in-depth analysis of their perceptions, attitudes, and actual effects on the innovative management model of community co-management. At the same time, it provides empirical evidence and theoretical support for the construction of a more reasonable, efficient, and win–win nature reserve management model. Based on field research and interviews, combined with a questionnaire survey of stakeholders, this study utilized the Q method to conduct a comprehensive analysis of household perceptions under community co-management. The research results indicate that community co-management is an effective path to promote the coordinated development of the local economy, society, and ecology. Specifically, this model not only significantly promotes employment and entrepreneurship among community residents but also achieves economic self-sufficiency and steady growth by cultivating characteristic industries and building distinctive brands. Further analysis reveals that improving residents’ well-being is the core value of community co-management. Meanwhile, system reform is seen as the key to promoting the deepening development of community co-management. This study not only helps to enhance households’ understanding and participation in ecological protection and promotes the deep integration of ecological protection and community development but also provides valuable experience and inspiration for the management of nature reserves in other regions around the world.